Chamber Theatre - Karen Walton (Law Text Culture, 2010)
A child of a defendant is called to his defence. As the child begins to murmur his evidence the judge orders him to speak up. The child looks across at the defendant, his father, the man who is meant to be his protector. But now the father, speaking through words of his defence barrister, accuses the child. The child looks to see if he is saying the right script to exculpate his father, and thereby betrays his innocence to the theatre of the courtroom. The jury, the judge, the defence barrister see this exchange and at this point the case is proved and a truth is decided upon. In a trial such as this, where allegations of a sexual nature are made, the story is played in intimate, yet clinical detail, in front of a room full of strangers.